Being overweight or obese is associated with harboring a gut microbial community not capable of metabolizing the soy isoflavone daidzein to O-desmethylangolensin in peri- and post-menopausal women. (May 2017) - Miller, Lindsey M.; Lampe, Johanna W.; Newton, Katherine M.; Gundersen, Gabrielle; Fuller, Sharon; Reed, Susan D.; Frankenfeld, Cara L.
Highlights: Being a non-producer of the gut bacteria-produced soy metabolite O- desmethylangolensin was significantly associated with a higher prevalence of obesity in peri- and post-menopausal women. This relationship between being an O- desmethylangolensin non-producer and obesity was similar across peri- and post-menopausal women. Being a non-producer of the gut bacteria-produced soy metabolite equol was not significantly associated with obesity in peri- and post-menopausal women. Abstract: Objective: Obesity can be a considerable health concern for peri- and post-menopausal women. Evidence suggests an association between the gut microbiome and obesity. The study objective was to evaluate the association between being overweight or obese and phenotypic markers of having an overall gut microbial environment not capable of metabolizing the isoflavone daidzein to equol or O- desmethylangolensin (ODMA). Study design: Cross-sectional study of 137 peri- and 218 post-menopausal women, aged 44–55 years, who consumed at least three servings per week of soy (source of daidzein). Equol and ODMA producers and non-producers were identified based on urinary concentrations of daidzein, equol and ODMA in a 24-h urine sample. Main outcome measures: Mean body mass index (BMI) and odds of obesity. Results: Fifty-one women were ODMA non-producers and 226 were equol non-producers. The ODMA non-producer phenotype was positively associated with obesity (OR: 3.33, 95% CI: 1.53, 7.23), and mean BMI was significantly higher in non-producers (28.9 kg/m 2 ) than in producers (26.7 kg/m 2 ), after adjusting for age, ethnicity, and menopausal status. Positive associations with being obese were observed in both peri-menopausal (OR = 3.92, 95% CI: 0.90, 17.0) and post-menopausal (OR = 3.00, 95% CI: 1.22, 7.70) women. The equol non-producer phenotype was not associated with obesity (OR = 1.13, 95% CI: 0.64, 1.98), and mean BMI was not significantly different between equol producers (27.3 kg/m 2 ) and non-producers (26.5 kg/m 2 ). Conclusions: These results suggest that the ODMA non-producer phenotype is associated with obesity in peri- and post-menopausal women. Further work is needed to confirm these observations in additional populations and to evaluate possible mechanisms.